Restabelecimento da barreira morfo-funcional intestinal através da suplementação com glutamina, alanil-glutamina e peptídeos, em camundongos com mucosite induzida por 5-fluorouracil - Monteiro, Manuel Carlos Serra Azul (2006)
Pathological disturbances and antineoplasic drugs like 5-Fluorouracyl (5-FU) cause consequences of diarrheal diseases. Intestinal barrier must be preserved to absortive functions. Antiproliferative action of 5-FU results of apoptosis upon DNA lesion. In order to investigate the intestinal mucositis 5-FU-induced and the efficacy of glutamine (Gln), alanyl-glutamine (Ala-Gln), hyprol 4107 (HYP), hyfoama 77 (HYFO) supplementation, on this clinical condition, we used intestinal perfusion approach in mice (n=344) and rabbits (n=72). To evaluate Gln, Ala-Gln, Hyprol 4107 and Hyfoama 77, we used morphometric, metabolic techniques and intestinal permeability test (lactulose/mannitol, L/M). Intestinal mucositis induced by 5-FU in mice was validate by diarrhea occurence and impaired nutritional status (-1,88 ± 0,537 g) establishments, after 3 thd day of 5-FU treatment. Morphometric analysis of duodenum and jejunum, demonstrated a flattening villous (251±6,07 µm) and hyperplasic crypts (128,3±4,98 µm), as well as a increase in apoptosis (13,5±1,89/crypt). L/M rate was greater in 5-FU group than control group (0,27±0,05). Gln, Ala-Gln and peptides improved weight gain and a food intake in mucositis model. Nutrients supplementation reduces morphologic alteration and the increased apoptosis (0,25±0.05). No changes were observed at intestinal mitosis profile, upon 3 thd day of 5-FU treatment. This supplementation improved transcellular and paracellular routs by establishment of intestinal permeability (0.35 to 0.73) in mucositis. Our results suggest that the improvement of intestinal barrier function was induced by an increase energy substrate to enterocyte, inhibition of apoptosis in crypts. So we suggest that gln and peptides supplementation could prevent the malnutrition, reduce diarrheal diseases and ameliorate intestinal barrier function.